2008
DOI: 10.1681/asn.2007101142
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Urinary Potassium Excretion

Abstract: Racial differences in potassium (K) intake and urinary K excretion may contribute to the higher BP observed in black compared with white individuals. Although black individuals typically consume less dietary K than white individuals, the lower urinary K excretion observed in black individuals may reflect more than differences in intake. In this study, data from the Dietary Approaches to Stop Hypertension (DASH) trial (413 white and black participants) were used to evaluate urinary K excretion in black and whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 30 publications
2
52
1
Order By: Relevance
“…Another recent study showed lower 24-h urinary potassium excretion rates for black than white women (35). This finding has now been extended to men as well (36). Among participants in the Dietary Approaches to Stop Hypertension (DASH) study, urinary potassium excretion was lower in black individuals, a phenomenon that persisted despite low potassium diet, suggesting that factors other than dietary intake are responsible.…”
Section: Discussionmentioning
confidence: 92%
“…Another recent study showed lower 24-h urinary potassium excretion rates for black than white women (35). This finding has now been extended to men as well (36). Among participants in the Dietary Approaches to Stop Hypertension (DASH) study, urinary potassium excretion was lower in black individuals, a phenomenon that persisted despite low potassium diet, suggesting that factors other than dietary intake are responsible.…”
Section: Discussionmentioning
confidence: 92%
“…Previous data raise the interesting question of whether differences in intake between races are primary, or secondary and subsequent to primary differences in renal tubular handling and excretion, or due to differences in gastrointestinal absorption. Turban et al (11) reported that baseline urinary K + excretion was significantly lower in blacks compared with whites, which was maintained after an 8-week consumption of the DASH diet. One proposed mechanism is augmented furosemide-sensitive Na + -K + -2Cl 2 cotransporter activity in the thick ascending limb of Henle's loop in blacks, which leads to increased fractional Na + reabsorption upstream to the location of the epitheliumlike sodium channel, reducing tubular flow and Na + delivery and resulting in less K + excretion (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of primary hypertension is still not well understood, a variety of modifiable factors such as diet, especially one high in sodium (Na + ) and low in potassium (K + ) content, have been implicated as mechanisms. Classic studies and observational data implicate that the combined effect of low K + and high Na + on BP seems greater than either alone, especially in blacks or African Americans (5)(6)(7)(8)(9)(10)(11)(12)(13). We suggested a role for WNK1 (with no lysine [K]) as a mediator of renal Na + retention and salt-sensitive hypertension in a state of dietary K + deficiency (12,13).…”
Section: Introductionmentioning
confidence: 86%
“…African Americans have a higher prevalence of both diabetes and prediabetes (10,11), and potassium homeostasis may contribute to these disparities. Potassium homeostasis differs by race (12)(13)(14)(15)(16), and the association between low-normal serum potassium and increased diabetes risk has been found to be stronger in African Americans than in whites (6,17). If relative hypokalemia is a potential risk factor for diabetes and a contributor to the racial disparity in diabetes risk, then potassium supplementation, dietary or pharmacologic, which is a potentially inexpensive, well-tolerated, and simple intervention, could improve glucose metabolism and potentially reduce diabetes risk, especially in this high-risk population.…”
Section: Introductionmentioning
confidence: 99%